Teknik “Get Out”, “Let It Out”, dan “Think It Out”: Intervensi regulasi emosi untuk remaja dengan perilaku menyakiti diri - Widiastini, Made Nisa Adriana; Moeliono, Marisa Fransiska (Procedia : Studi Kasus dan Intervensi Psikologi, 2024)
The phenomenon in Indonesia shows the high prevalence of self-harming behavior in teenagers. Self-harm behavior is defined as a form of behavior that involves the destruction of body tissue carried out consciously and deliberately without any desire to end one's life. This research aims to determine the effectiveness of the Get Out, "Let It Out", and "Think It Out" interventions to improve emotional regulation skills to reduce decision-making that leads to self-harming behavior. The subject of this research is a 16-year-old female teenager who injured herself. Yourself by cutting your arm. The assessment method used is interviews to collect in-depth information about subject problems. Observation to determine the subject's condition directly during the assessment process. Psychological tests include intelligence tests, questionnaires to obtain information regarding motives for self-harm behavior, and emotional regulation strategies used. The results of the assessment concluded that the subject met the diagnostic criteria for non-suicide self-injury. The intervention was carried out using the "Get Out", "Let It Out", and "Think It Out" techniques which are related to four emotional regulation strategies. The results of the intervention showed that subjects were able to apply more adaptive emotional regulation strategies so that they were effective in helping stop self-harming behavior. It is hoped that the results of this research can develop psychological science, especially in dealing with Indonesian teenagers involved in self-harming behavior.Fenomena di Indonesia menunjukkan tingginya angka prevalensi perilaku menyakiti diri sendiri pada remaja. Perilaku merugikan diri sendiri didefinisikan sebagai bentuk perilaku yang melibatkan perusakan jaringan tubuh yang dilakukan secara sadar dan disengaja tanpa adanya keinginan untuk mengakhiri hidupnya. Tujuan penelitian ini adalah untuk mengetahui efektifitas intervensi Get Out”, “Let It Out”, dan “Think It Out untuk meningkatkan keterampilan regulasi emosi guna mengurangi pengambilan keputusan yang mengarah pada perilaku menyakiti diri Subjek penelitian ini adalah seorang remaja perempuan berusia 16 tahun yang melukai diri dengan cara menyayat lengan. Metode asesmen yang digunakan adalah wawancara untuk mengumpulkan informasi mendalam terkait permasalahan subjek. Observasi untuk mengetahui kondisi subjek secara langsung selama proses asesmen. Tes psikologi meliputi tes kecerdasan, kuesioner untuk mendapatkan informasi terkait motif perilaku menyakiti diri, dan strategi regulasi emosi yang digunakan. Hasil dari asesmen menyimpulkan subjek memenuhi kriteria diagnostik non-suicide self-injury. Intervensi dilakukan dengan teknik “Get Out”, “Let It Out”, dan “Think It Out” yang berhubungan dengan empat strategi regulasi emosi. Hasil intervensi menunjukkan bahwa subjek dapat menerapkan strategi regulasi emosi yang lebih adaptif sehingga efektif membantu menghentikan perilaku menyakiti diri sendiri. Hasil penelitian ini diharapkan dapat mengembangkan keilmuan psikologi terutama dalam menghadapi remaja Indonesia yang terlibat perilaku menyakiti diri sendiri.